Behaviour and Welfare of Indigenous Poultry Breeds (Indian Journal of Animal Production and Management, 2024)
Poultry production has undergone an  enormous expansion and development during last  few decades through advances in genetics,  nutrition and husbandry which have resulted in  improving the productivity. Consequently, the  poultry industry has emerged as one of the most  dynamic and fastest expanding segments in animal  husbandry. It plays a significant role in providing  households with a source of nutritious food, income  generation, and livelihood support especially in  backyard farming systems. Backyard poultry  farming is deeply ingrained in cultural practices and  poultry birds have cultural and religious  significance. Poultry production in India faces  several challenges including limited access to  veterinary services, biosecurity issues, vulnerability  to diseases and high mortality. This paper briefly  discusses the behaviours of indigenous poultry  birds, its assessment protocols, concepts and  indicators of poultry welfare, international welfare  guidelines and regulations. The paper also  highlights the poultry welfare standards, welfare  issues in India and offers a strategy for the  mitigation of poultry welfare problem in India.
Keywords: poultry behaviour; welfare; assessment; welfare standards